Random access scheme for different MTC scenario requirement - Zhefu WU; Xinyuan YANG; Wenchao ZHAI; Huimei HAN (Tongxin xuebao)
For the different random access requirements of the mixed scenarios of ultra-reliable low latency (URLLC) and massive machine type communications (mMTC) in MTC,a random access scheme based on devices grouping was proposed.The proposed scheme divided the MTC devices into several groups based on the timing advance (TA) information:for the URLLC scenario,preamble resources were reserved for core devices in each group,and the URLLC devices accessed the network via the contention-free mechanism,to satisfy the ultra-reliable low latency access requirement; for the mMTC scenario,the base station utilized the different TA information in different group to identify devices selecting the same preamble,and performed successive interference cancellation (SIC) algorithm to detect the data information,to satisfy the massive access requirement.Simulation results demonstrate that the proposed scheme can significantly increase the number of the successful devices.